Primary Healthcare Physicians’ Knowledge and Attitude Toward Obstructive Sleep Apnoea in the Qassim Region, Saudi Arabia - Alharbi, Fahad Sinhat; Kalevaru , Chandra Sekhar (Scripta Medica, 2025)
Background/Aim: Obstructive sleep apnoea (OSA) is a prevalent disorder worldwide. The prevalence is increasing as obesity becomes more common. OSA is also related to different serious conditions such as cardiovascular diseases and cerebrovascular diseases. Although it’s a common condition OSA is underdiagnosed and undertreated. The aim of the study was to assess primary healthcare physicians (PHC) knowledge and attitude toward obstructive sleep apnoea and examine their relationship with demographic variables in the Qassim region. Methods: A cross-sectional study design was used among 190 PHC physicians in the Qassim region. Data was collected through a validated self-administered online questionnaire distributed to 325 PHC centre physicians and the response rate was 58.4 %. Data was analysed using the SPSS 21.0 version. For inferential statistics, the Chi-square test and independent t-test were applied. Results: A total of 190 physicians participated in this study, with the majority being male (56 %) and an average age of 39 ± 9.18 years. The findings revealed that 67.9 % of participants had insufficient knowledge about OSA. However, physicians with higher education and more experience demonstrated significantly better knowledge (69.7 %) compared to those with lower qualifications and less experience (24.2 %) (p < 0.001). Regarding attitudes, 54.2 % of PHC physicians exhibited a positive attitude toward OSA. Notably, family medicine specialists and consultants had a significantly more positive attitude (69.7 %) compared to general practitioners and family medicine residents (51.0 %) (p < 0.05). Conclusion: Overall, PHC physicians in the Qassim region have inadequate knowledge about OSA, with more experienced and highly educated physicians demonstrating better understanding. While the overall attitude toward OSA is positive, specialists and consultants exhibit a significantly more favourable perspective than general practitioners and residents. Lectures and seminars about OSA are to be held to help physicians who didn’t have adequate postgraduate training to improve their practice.